2017
DOI: 10.1111/jocn.13455
|View full text |Cite
|
Sign up to set email alerts
|

The examination of problems experienced by nurses and doctors associated with exposure to surgical smoke and the necessary precautions

Abstract: Attention brought to the effects of surgical smoke. Presentation of the harmful effects of surgical smoke reported by doctors and nurses. Identification of the precautions that can be taken against surgical smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 17 publications
(53 reference statements)
3
69
2
17
Order By: Relevance
“…Studies during the past four decades has demonstrated that surgical smoke generated from the use of energy-generating devices in surgery contained toxic and biohazardous substances that present health risks to perioperative team members and patients [23]. The other argument was that surgeon long-term exposure to the surgical smoke could directly affect the surgical quality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies during the past four decades has demonstrated that surgical smoke generated from the use of energy-generating devices in surgery contained toxic and biohazardous substances that present health risks to perioperative team members and patients [23]. The other argument was that surgeon long-term exposure to the surgical smoke could directly affect the surgical quality.…”
Section: Discussionmentioning
confidence: 99%
“…Xylene, toluene and ethylbenzene components have been suggested to induce headache and eye pain . In a survey conducted to assess the adverse effects of surgical smoke experienced by theatre staff, 58.3% of doctors and 48.9% of nurses reported headache, 41.7% of doctors and 40% of nurses complained of problematic lacrimation, and more than 20% of staff were affected by cough . Sore throat, sneezing, rhinitis, odours absorbed into hair, nausea, drowsiness and dizziness were also reported .…”
Section: Clinical Effectsmentioning
confidence: 99%
“…In addition, and also of significant concern, this smoke may contain hydrogen cyanide, formaldehyde, benzene and virus particles 1 . Many research studies 1,13,21 have expressed concern related to the impact of surgical smoke on the perioperative care team's health, especially in relation to respiratory problems.…”
Section: Surgical Smoke Hazardsmentioning
confidence: 99%
“…A number of studies 1,5,10,12,13 have revealed specific surgical hazards associated with the perioperative health care team's exposure to surgical smoke, and some of the symptoms associated with this exposure are listed below 5,10,13,21 .…”
Section: Health Problems Associated With Surgical Smokementioning
confidence: 99%
See 1 more Smart Citation